On Spaces of Boundary Values for Relations Generated by a Formally Selfadjoint Expression and a Nonnegative Operator Function - Bruk, V. M. (Журнал математичної фізики, аналізу, геометрії, 2006)
The space of boundary values for a maximal relation generated by a formally selfadjoint differential expression and a nonnegative operator function is constructed. Mathematics Subject Classification: 47A06, 34B05.